2023
DOI: 10.1038/s41392-023-01720-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting epigenetic and posttranslational modifications regulating ferroptosis for the treatment of diseases

Yumin Wang,
Jing Hu,
Shuang Wu
et al.

Abstract: Ferroptosis, a unique modality of cell death with mechanistic and morphological differences from other cell death modes, plays a pivotal role in regulating tumorigenesis and offers a new opportunity for modulating anticancer drug resistance. Aberrant epigenetic modifications and posttranslational modifications (PTMs) promote anticancer drug resistance, cancer progression, and metastasis. Accumulating studies indicate that epigenetic modifications can transcriptionally and translationally determine cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 622 publications
0
9
0
Order By: Relevance
“…The current mechanism of RNA methylation regulating ferroptosis is mainly focused on the classical SLC7A11-GPX4 axis, and RNA methylation modifications in non-classical ferroptosis regulatory mechanisms need to be further investigated. An increasing number of epigenetic modifications that induce or inhibit ferroptosis targets are being identified, and combinations of epigenetic drugs with other conventional therapies are used in preclinical studies and clinical testing [12]. MiR-101-3p and E/M@FA-LP nanomedicines have promising antitumor effects in treating ferroptosis-associated tumors [108,143].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The current mechanism of RNA methylation regulating ferroptosis is mainly focused on the classical SLC7A11-GPX4 axis, and RNA methylation modifications in non-classical ferroptosis regulatory mechanisms need to be further investigated. An increasing number of epigenetic modifications that induce or inhibit ferroptosis targets are being identified, and combinations of epigenetic drugs with other conventional therapies are used in preclinical studies and clinical testing [12]. MiR-101-3p and E/M@FA-LP nanomedicines have promising antitumor effects in treating ferroptosis-associated tumors [108,143].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…MiR-101-3p and E/M@FA-LP nanomedicines have promising antitumor effects in treating ferroptosis-associated tumors [108,143]. However, the modulation of ferroptosis through treatment with the same epigenetic modifications may show opposite effects in different tissues or diseases [12,50]. Epigenetic factors involve the development and progress of cancer and other diseases by regulating ferroptosis-associated genes.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of HSCs is a central event during hepatic fibrosis. Ferroptosis is a new type of iron-dependent non-apoptotic cell death, inhibition of p53-mediated HSC ferroptosis has been shown to promote hepatic fibrosis by triggering ECM deposition and HSC activation [ 89 91 ]. Lujambio et al found that in CCl4-treated mice, HSC-specific deletion of p53 exhibits an excessive accumulation of collagen production and an overall decreased senescent HSCs, indicating that p53 accumulation in HSCs can ameliorate hepatic fibrosis by promoting HSC senescence [ 92 ].…”
Section: Roles Of P53 In Organ Fibrosismentioning
confidence: 99%
“…Abnormal PTMs can lead to changes in protein properties and loss of protein function. These changes are closely associated with the development and progression of many diseases ( 23 ). The PTM of a variety of proteins (e.g., Phosphorylation, ubiquitination, acetylation, and methylation) also plays an integral regulatory role in ferroptosis ( 24 ).…”
Section: Introductionmentioning
confidence: 99%